A Predictive Algorithm to Detect Opioid Use Disorder: What Is the Utility in a Primary Care Setting?. (16th January 2018) - Lee, Chee; Sharma, Maneesh; Kantorovich, Svetlana; Brenton, Ashley
Purpose: The purpose of this study was to determine the clinical utility of an algorithm-based decision tool designed to assess risk associated with opioid use in the primary care setting. Methods: A prospective, longitudinal study was conducted to assess the utility of precision medicine testing in 1822 patients across 18 family medicine/primary care clinics in the United States. Using the profile, patients were categorized into low, moderate, and high risk for opioid use. Physicians who ordered testing were asked to complete patient evaluations and document their actions, decisions, and perceptions regarding the utility of the precision medicine tests. Results: Approximately 47% of primary care physicians surveyed used the profile to guide clinical decision-making. These physicians rated the benefit of the profile on patient care an average of 3.6 on a 5-point scale (1 indicating no benefit and 5 indicating significant benefit). Eighty-eight percent of all clinicians surveyed felt the test exhibited some benefit to their patient care. The most frequent utilization for the profile was to guide a change in opioid prescribed. Physicians reported greater benefit of profile utilization for minority patients. Patients whose treatment was guided by the profile had pain levels that were reduced, on average, 2.7 levels on the numeric rating scale. Conclusions: The profile provided primary care physicians with a useful tool to stratify the risk of opioid use disorder and was rated as beneficial for decision-making and patient improvement by the majority of physicians surveyed. Physicians reported the profile resulted in greater clinical improvement for minorities, highlighting the objective use of this profile to guide judicial use of opioids in high-risk patients. Significantly, when physicians used the profile to guide treatment decisions, patient-reported pain was greatly reduced.